The Existence of Province Branding to Communicate The Potency and Positioning of East Java Province, Indonesia - Faizza, Emil (STISIPOL Raja Haji, 2021)
Referring to the various concepts, theories and researches, branding in a region is a necessity. The need to create differentiation to make strong positioning, to create a positive perception of the related province so that the public does not create their own perception of the province, to introduce all potency and to market the region to the target market as well as domestic and foreign tourists as well as investors, both from within and outside the country. All of the fulfillment of these needs will impact on reducing levels of poverty and unemployment since the opening of jobs due to the inclusion of investment and the number of tourist visits. This will increase the level of economic and social welfare of the province. However, East Java, a big province in Indonesia with economic growth each year is above the average growth of the national economy and has contributed greatly to the economic condition in Indonesia as well as efficiency and high productivity of the investment coming in, did not have exist province branding. Therefore, author will write how the existence of province branding in communicating the potency and positioning of East Java. Whether region can grow without exist branding and break the concept and the theory of branding over the years.